Egy Gogol-szöveghely Puskin-hivatkozásáról: A démon című költemény szerepe Az arcképben - Kroó, Katalin (Slavia Centralis, 2020)
Gogol's text as a reference to Pushkin: The function of Pushkin's poem (The Demon in Gogol's The Portrait)This article examines the function of an allusion to Pushkin’s poem The Demon in Gogol’s The Portrait. It reveals that the Pushkin intertext shows special features in Gogol’s short story, since it is not primarily alongside thematic definitions or motif formulations that the intertext envolves, but much more significantly, at a metatextual level. This meaning layer is fairly complex, as it develops the sense of a kind of art definition in two major directions: taking into account the relationship of life to art, and the ever developing artistic languagewhich never ceases to recreate itself. As a result of a survey of the semantic processes constructing the metapoetic reading of Gogol’s The Portrait, the conclusion is drawn that Pushkin’s The Demon and Gogol’s demon(s) semantically incorporate a similarly wide range of meaning, which can be regarded as the semantic code of the genesis of certain texts of Pushkin and Gogol.
Keywords: Pushkin’s The Demon; Gogol’s The Portrait; intertextuality; metapoetic reading; life–art relation; literary language creation